The Impact of Flash Cards on Student Learning Outcomes in Science Education - Rusita, Rusita; Rahman, Rahman (Juwara: Jurnal Wawasan dan Aksara, 2024)
ABSTRAK Peneltian ini bertujuan untuk mengetahui dampak penggunaan Media Flash Card pada hasil belajar IPA oleh siswa kelas V di SD Negeri 6 Jarai. Studi ini menggunakan metode eksperimental dengan rancangan pre-experimental, khususnya one group pretest-posttest design. Populasi meliputi seluruh murid dari kelas I hingga VI di sekolah yang sama, dengan sampel penelitian terdiri dari 25 siswa kelas V. Analisis data awal menunjukkan bahwa hanya 7 dari 25 siswa (29,16%) yang mencapai kriteria ketuntasan minimal (KKM) sebelum penerapan Flash Card, dengan nilai rata-rata klasikal 66,66%. Setelah penerapan, 20 dari 25 siswa (83,33%) berhasil memenuhi KKM dengan rata-rata nilai meningkat menjadi 83,12%. Hasil uji statistik t menghasilkan t-hitung sebesar 7,06, melebihi t-tabel 2,06, yang mengindikasikan penolakan H0 dan penerimaan Ha. Hal ini membuktikan bahwa penggunaan Media Flash Card efektif dalam meningkatkan hasil belajar IPA siswa tersebut. ABSTRACT This research investigates the influence of incorporating Flash Card Media on the academic achievements in science of fifth-grade students at SD Negeri 6 Jarai. The study utilised an experimental approach with a pre-experimental design, notably the one-group pretest-posttest design. The population comprised all students enrolled in grades I to VI at the same educational institution, while the research sample consisted of 25 kids in the fifth grade. Initial data analysis revealed that prior to applying Flash Cards, only 7 out of 25 students (29.16%) achieved the minimum mastery criteria (KKM), with an average classical score of 66.66%. Following the implementation, 83.33% of the students, namely 20 out of 25, reached the KKM (minimum passing grade), resulting in an average score improvement of 83.12%. The t-test returned a t-calculated value of 7.06, which surpasses the critical t-value of 2.06 from the t-table. This indicates that we can reject the null hypothesis (H0) and accept the alternative hypothesis (Ha). This demonstrates the efficacy of utilising Flash Card Media in improving the science learning results of these pupils.